2022
DOI: 10.1038/s41598-022-25559-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of rice supply chain supervision model driven by blockchain smart contract

Abstract: The outbreak of the COVID-19 and the Russia Ukraine war has had a great impact on the rice supply chain. Compared with other grain supply chains, rice supply chain has more complex structure and data. Using digital means to realize the dynamic supervision of rice supply chain is helpful to ensure the quality and safety of rice. This study aimed to build a dynamic supervision model suited to the circulation characteristics of the rice supply chain and implement contractualization, analysis, and verification. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Peng et al [ 62 ] presented a dynamic supervision model for the rice supply chain, including an initialization module, a supervision module, and a storage module ( Figure 3 ). The initialization module classifies participants into enterprises, consumers, and regulatory agencies, further splitting enterprises into six categories and sub-nodes.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peng et al [ 62 ] presented a dynamic supervision model for the rice supply chain, including an initialization module, a supervision module, and a storage module ( Figure 3 ). The initialization module classifies participants into enterprises, consumers, and regulatory agencies, further splitting enterprises into six categories and sub-nodes.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Collecting environmental data through IoT devices also provides insights for optimizing farming practices, including irrigation and fertilization decisions, thereby improving farm productivity [ 60 , 61 , 62 , 63 , 64 ]. The marriage of blockchain and big data secures data exchange and provides timely demand information, drawing significant attention from stakeholders and promising substantial benefits in risk minimization [ 69 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Credit supervision is introduced to agricultural product quality and safety, and a credit supervision and assessment system is established around the behavior of agricultural subjects to guarantee agricultural product quality and safety. The blockchain-based credit assessment smart contract regulatory model can realize dynamic and credible supervision of the entire life cycle of the supply chain at the information level, and its application to the digital management of the agricultural supply chain can strengthen the digital regulation of the agricultural industry (Peng et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…the complexity of these factors poses a significant challenge" [1] (p. 1). For example, Peng et al [2] identified approximately 13 steps in the rice supply chain from the plant to purchase, storage, processing, transport, storage, and sale. Therefore, the food system's complexity represents a unique context within which individual actors may include smallholder farmers, commercial scale farmers, input providers such as seed and fertilizer individuals, financial service providers, policymakers, or food system regulators [3].…”
Section: Introductionmentioning
confidence: 99%